Multimodal data visualization method for digital twin campus construction - Yakun Xie; Ni Zhan; Qing Zhu; Junjie Zhan; Zhihao Guo; Changjian Qiao; Jun Zhu; Bingli Xu (International Journal of Digital Earth)
University campuses, as distinctive yet commonplace urban environments, face similar challenges of high population density and efficient management. Integrating digital twins into smart campus construction is essential for optimizing campus management. Multimodal data integration and visualization are key to building a digital twin campus. Traditional visualization methods often lack effective inter-data relationships, limiting their capacity to support robust multimodal data integration and create a multidimensional, real-time, comprehensive management view. Therefore, this paper proposes a tailored approach for multimodal data integration and visualization in digital twin campus construction. First, a comprehensive analysis of multimodal campus data identifies spatiotemporal associations among datasets. Subsequently, visualization strategies are developed based on these data characteristics and associations, enabling the multidimensional integration of 3D models, video surveillance, and wireless sensor data. Finally, a prototype system is implemented and evaluated through a case study. The results demonstrate that the proposed method efficiently integrates 2D maps, surveillance videos, and sensor data to create a dynamic, interactive, and panoramic campus view, achieving rendering efficiency exceeding 60 frames per second. Moreover, this adaptable framework can be applied to various campus or geographic contexts, offering critical technical support for multimodal visualization in IoT and big data environments.